Maize - Production and Use 2020
DOI: 10.5772/intechopen.90033
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Impacts on Sustainable Maize Production in Sub-Saharan Africa: A Review

Abstract: Maize (Zea mays L.) is one of the commonly grown grain crops and remains a source of staple food and food security for most countries in sub-Saharan Africa (SSA). But climate change threatens agricultural potential in SSA thereby risking food security especially that most maize production is rain-fed in these countries. Thus, numerous studies have examined impacts of climate change on maize production and productivity resulting in several adaption strategies being promoted to mitigate the negative effects of c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 26 publications
(50 reference statements)
1
13
1
Order By: Relevance
“…Also, the use of combined climate information can improve the understanding of the relationship between crop production and the weather oscillations and improve the resilience of the global food system (food security) to unexpected climate-related shocks [16,[56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the use of combined climate information can improve the understanding of the relationship between crop production and the weather oscillations and improve the resilience of the global food system (food security) to unexpected climate-related shocks [16,[56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Projected future changes in temperature and rainfall directly threaten the overall agricultural crop production system (Arslan, 2018;Jain, 2007) because over 90% of smallholder agriculture production in Zambia is rainfed with only about 3% of the total planted area being irrigated (Hamududu & Ngoma, 2020). For example, 70-80% of maize crop losses in sub-Saharan Africa are attributed to climate changeenhanced droughts and floods, which makes maize one of the most susceptible crops to climate change (Mulungu & Ng'ombe, 2020). Several studies have reported that maize will be among the most negatively affected crops due to anticipated future climate patterns with measurable consequences on food security (Adhikari et al, 2015;Chisanga et al, 2017;Jones & Thornton, 2003;Mulenga et al, 2015;Thornton et al, 2011;Wang et al, 2015;Wineman & Crawford, 2017;Zipper et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, it follows that there is a growing body of research investigating the impacts of climate change adaptation strategies in Zambia and across sub-Saharan Africa (SSA). Examples of such studies include [15][16][17][18][19][20][21][22][23][24][25][26]. However, the limited capacity of smallholder farmers to adapt to climate change in Zambia [4,25] in part contributes to the low adoption rates of climate change adaptation measures [19,21].…”
Section: Introductionmentioning
confidence: 99%